Green finance and gender equality: Keys to achieving sustainable development - Fu-Hsaun Chen (Green Finance)
This research investigates the relationship between Green Finance (GF) and Gender Equality (GE) within the context of sustainable development, revealing that existing frameworks lack an integrated approach to incorporating GE into GF. By reviewing 125 relevant articles published from 2004 to 2024, the author also found that women's empowerment significantly promotes GF development, while gender diversity enhances environmental management and corporate performance. Furthermore, the contributions of women in climate adaptation and environmental sustainability should not be overlooked. In conclusion, there is a pressing need to incorporate a gender perspective into GF policies and practices, which calls for further exploration of gender-sensitive financing models and the culture impact on GF and GE, aiming to achieve the Sustainable Development Goals (SDGs) more effectively.